Microbiological and physical-chemical characteristics of fermented milk beverages - Andrade, E.H.P.; Silva, N.M.A.; Resende, M.F.S.; Souza, M.R.; Fonseca, L.M.; Cerqueira, M.M.O.P.; Penna, C.F.A.M.; Leite, M.O. (Arquivo brasileiro de medicina veterinária e zootecnia, 2015)
This study aimed to evaluate some microbiological and physical-chemical characteristics of fermented milk beverages collected at the main supermarkets in Belo Horizonte (MG). 40 samples of the products corresponding to five distinct brands were collected. They were submitted to the following analyses: Most Probable Number (MPN) of total (30ºC) and thermal tolerant coliforms (45ºC), Salmonella spp., coagulase positive Staphylococcus, molds and yeasts, lactic acid bacteria, pH, titratable acidity and contents of moisture, total solids, protein and fat. The analyses were carried out during the last week of shelf life. The microbiological quality of the samples was good and the counts of lactic bacteria were above the minimum established by the official legislation. Streptococcus and Lactobacillus were isolated and identified from the products and Lactobacillus delbrueckii was molecularly identified in three samples. The mean values for the contents of fat and protein, titratable acidity, pH, moisture and total solids ranged from 1.24 to 1.98%; 1.88 to 2.22%; 0.54 to 0.66%; 3.91 to 4.16; 81.18 to 83.25% and 16.75 to 18.82%, respectively. All samples had protein content in agreement with the official legislation. RESUMO O objetivo do presente trabalho foi avaliar as características microbiológicas e físico-químicas de bebidas lácteas fermentadas. Foram coletadas 40 amostras de bebidas lácteas fermentadas pertencentes a cinco marcas distintas, em grandes redes de supermercados de Belo Horizonte. Em cada amostra, foram avaliados os seguintes parâmetros: número mais provável de coliformes totais (30ºC), número mais provável de coliformes termotolerantes (45ºC), pesquisa de Salmonella spp., contagem de Staphylococcus coagulase positiva, contagem de bolores e leveduras, contagem total de bactérias lácticas viáveis, umidade, sólidos totais, teor de proteína, teor de gordura, pH e acidez titulável. As análises foram realizadas na última semana do período de validade. As amostras apresentaram qualidade microbiológica satisfatória, bem como contagens totais de bactérias lácticas viáveis superiores ao mínimo estabelecido pela legislação. Streptococcus e Lactobacillus foram identificados em todas as marcas de bebidas lácteas fermentadas analisadas, e em três delas foi possível identificar a espécie Lactobacillus delbrueckii. Os valores médios encontrados para os teores de gordura, proteína, acidez titulável, pH, umidade e sólidos totais variaram de 1,24 a 1,98%, 1,88 a 2,22%, 0,54 a 0,66%, 3,91 a 4,16, 81,18 a 83,25% e 16,75 a 18,82%, respectivamente. Todas as marcas de bebidas lácteas fermentadas apresentaram teor médio de proteína superior ao mínimo preconizado pela legislação.